2020
DOI: 10.1177/1055665620966198
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Babbling and Early Consonant Development Related to Hearing in Children With Otitis Media With Effusion With or Without Cleft Palate

Abstract: Objective: To investigate and compare babbling, early consonant production and proficiency from 10 to 36 months of age and its relationship with hearing in children with otitis media with effusion (OME) with or without cleft palate. Design: Prospective, longitudinal group comparison study. Setting: University hospital. Participants: Fifteen children born with nonsyndromic cleft palate with or without cleft lip (CP±L) and 15 age-matched children with hearing loss (HL) associated with OME but without cleft palat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…It has been argued that the influence of an otitis media with effusion related hearing loss on speech development is present at early ages (Broen et al., 1998; Lohmander et al., 2021), and may be at risk for delayed speech and language development (Hall et al., 2017; Schönweiler et al., 1999). Unfortunately, the hearing data in the present study were incomplete and could not be included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that the influence of an otitis media with effusion related hearing loss on speech development is present at early ages (Broen et al., 1998; Lohmander et al., 2021), and may be at risk for delayed speech and language development (Hall et al., 2017; Schönweiler et al., 1999). Unfortunately, the hearing data in the present study were incomplete and could not be included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Canonical babbling onset (usually around 7 months and overwhelmingly by 10 months in typically developing infants) is a necessary foundation for speech [20,36] and predicts speech disorders; significant delays occur in onset of canonical babbling in Williams Syndrome [37], deafness [38,39] [40], Down Syndrome [41], cleft palate [42,43], cerebral palsy [44], Fragile X syndrome [45], childhood apraxia of speech [46], and autism [47]. Other disorders related to language development have also been indicated as involving significant deficiencies in canonical babbling [48][49][50].…”
Section: Rationale For Studying Vocal Development In Tscmentioning
confidence: 99%
“…Although improvements are made following surgical repair of the palate (usually performed around 12 months of age; Shaw et al, 2019), some of these difficulties continue to be present in the speech of children with CP ± L. Specifically, they exhibit smaller consonant inventories and produce fewer oral stops in their meaningful and non-meaningful utterances compared with children without CP ± L (Jones et al, 2003). Hearing loss has recently been highlighted as a possible predictor of poor speech in individuals with CP ± L (Lohmander et al, 2021). Lohmander et al (2021) found mild hearing loss to impact presence of canonical babbling at 10 months of age, the number of different consonants produced at 12 months of age and to be related to consonant proficiency at 36 months in children with CP ± L. Moreover, repeated middle-ear infections resulting in fluctuating hearing sensations during the development of the central auditory system may result in atypical auditory processing (Asbjørnsen et al, 2005;Haapala et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Hearing loss has recently been highlighted as a possible predictor of poor speech in individuals with CP ± L (Lohmander et al, 2021). Lohmander et al (2021) found mild hearing loss to impact presence of canonical babbling at 10 months of age, the number of different consonants produced at 12 months of age and to be related to consonant proficiency at 36 months in children with CP ± L. Moreover, repeated middle-ear infections resulting in fluctuating hearing sensations during the development of the central auditory system may result in atypical auditory processing (Asbjørnsen et al, 2005;Haapala et al, 2015). Impaired auditory skills, such as auditory attention, processing words in a noisy background and temporal processing, have been related to problems with speech-language development (Haapala et al, 2015;van Eeden, 2023).…”
Section: Introductionmentioning
confidence: 99%